MANAGEMENT OF FOREIGN ECONOMIC ACTIVITIES OF UKRAINIAN ENTERPRISES UNDER CURRENT CONDITIONS: OPPORTUNITIES AND PERSPECTIVES - YURCHENKO, O. (Herald of Kyiv Institute of Business and Technology, 2024)
The study analyzed theoretical and practical aspects and developed recommendations for improving the process of managing the foreign economic activity of the enterprise in the conditions of globalization and martial law. The peculiarities of foreign trade of Ukrainian enterprises in the conditions of globalization and martial law are determined. The role of the European market in the restoration of logistics supply chains is characterized. An analysis of the indicators of export-import activity and the geographical structure of export-import operations in Ukraine during 2018–2022 was carried out. In order to increase the effectiveness of foreign economic activity, companies must first of all identify countries that are attractive for cooperation, study existing foreign economic ties and analyze the possibility of new cooperation. Companies should conduct an in-depth analysis of the international trade system and study the economic environment of the country they intend to enter, taking into account the political, cultural and legal characteristics of their environment. The need to improve the foreign economic activity of Ukrainian enterprises in the conditions of globalization and martial law, which is a task as a condition for ensuring the stability and development of the country’s economy, is substantiated. The directions for improvement of the EZ of Ukrainian enterprises in the specified conditions have been determined. It is substantiated that in order to increase the efficiency of foreign economic activity, companies should first of all identify attractive countries for cooperation, study existing foreign economic ties and analyze the possibility of new cooperation.